2004
DOI: 10.1055/s-2004-820342
|View full text |Cite
|
Sign up to set email alerts
|

Induktion von Knochengewebe auf unterschiedlichen Matrizes: Eine In-vitro- und In-vivo-Pilotstudie in der SCID Maus

Abstract: All three matrices promoted BMSC proliferation and differentiation to osteogenic cells in vitro. Human BMSC on CDHA showed signs of osteogenic differentiation after subcutaneous implantation into SCID mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Very little data has been published to date on the use of this cement in the form of granules for critical-size defects [19,20,29]. According to Bohner and Baumgart, the in vivo resorption rate of porous granules can be predicted to be much faster than in dense blocks or prismatic objects made out of the same material [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very little data has been published to date on the use of this cement in the form of granules for critical-size defects [19,20,29]. According to Bohner and Baumgart, the in vivo resorption rate of porous granules can be predicted to be much faster than in dense blocks or prismatic objects made out of the same material [30].…”
Section: Discussionmentioning
confidence: 99%
“…There have, however, so far only been a limited number of clinical and experimental studies conducted to test the feasibility of these CaP cement-granules, which are moreover difficult to compare with our animal model. In vitro cell culture tests [34-36] and only few in vivo implantations have been performed [19,20]. However, there is presently no in vivo study clearly demonstrating differences in performance between CaP cement-granules and sintered ceramic granules [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 47 On the other hand, it has been demonstrated that a highly interconnected pore network with high porosity could benefit cell growth, transport of nutrients and metabolic waste, the deposit of cellular matrix and the in growth of newly formed tissues. This result indicated that 20% DBM/SF scaffolds had the most prominent effect on cell attachment and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) staining was performed as described in the manufacturer's instructions (Rainbow, Shanghai, China). Meanwhile, ALP activity was determined at 405 nm using p-nitrophenylphosphate (pNPP) (Sigma-Aldrich) as the substrate, 19 while the total protein content was determined by the protein assay kit according to the protocol provided. 20 The ALP activity OD values were nally normalized to the total protein content OD values correspondingly.…”
Section: Osteogenic Differentiation Of Hbmscsmentioning
confidence: 99%